SABS : Spark ABStraction - A Tutorial - Miraldo, Victor Cacciari (2014)
SABS is a predicate abstraction laboratory that is beeing developed at University of Minho, Portugal. Our goal is not to produce a industrial software model checker, such as SLAM [BMR01] or SATABS [CKSY05], but to have a tool to study and compare the diferent techniques (and combination of techniques) that can be used to perform the predicate abstraction of a program, in our case, a SPARK program. This document is a both a tutorial on the usage of SABS and a (small) explanation of its implementation. Some knowledge on Predicate Abstraction and Program Verification is assumed, we refer the reader to [MLPF13] for some background on the techniques implemented by SABS.